PENGARUH KEPUTUSAN INVESTASI, KEBIJAKAN DIVIDEN, DAN KEPUTUSAN PENDANAAN TERHADAP NILAI PERUSAHAAN - Haryadi Krisnandar; Lukytawati Anggraeni; Hendro Sasongko (Jurnal Bina Bangsa Ekonomika, 2024)
Overall, the performance of retail companies in the capital market shows a downward trend in recent years. However, amid the decline, some retail companies still show optimism by investing to boost their business activities. This research will analyze the effect of investment decisions, dividend policies, and funding decisions made by retail companies on the value of their companies. Data from 21 companies from 2014-2018 used panel data regression. The results of the panel regression model concluded that the variables Return on Equity (ROE), Debt to Equity Ratio (DER), Debt To Asset Ratio (DAR) had a significant effect on Price per Book Value (PBV). Based on the results of the study, the main factor that needs to be considered by companies to be able to increase company value is financial performance, especially company profitability (ROE and ROA). Another factor that also needs to be considered by the company to increase the value of the company is the proportion of debt in the capital structure